Developing a System for IoT-Based Movement Induction Motor (International Journal of Food and Nutritional Sciences, 2022)
Due to its superior qualities as compared to others, induction motors, particularly three-phase induction motors, are often utilized in the industry. One of the newest technologies for improving the efficiency and dependability of motors is distant control converters. The Internet of Things has emerged as one of the primary methods to connect with various gadgets thanks to the rapid growth of technology and the development of the network connection. Internet connectivity has risen, particularly in industrial settings where it improves products monitoring and control. In this investigation, a manufacturing induction motor was analyzed utilizing a wireless TCP/IP interface, and differences from predicted operating conditions prior to an event happening by a motor were identified and estimated. This assists for the least number of disastrous repair and replacement while also preventing clogs in the construction system. In this study, the motorcycle's motor voltages, power flow, and Hall-effect reference voltage were measured. To do this, the established infrastructure evaluates the motor's findings and sends those data to a centralized monitoring system. This work will give details on IoT (Internet of Things)-based motion intelligence monitoring in the coming days, assisting and setting up an alternative route for other researchers' study.